2017
DOI: 10.1038/s41598-017-02816-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a Encapsulated in Hyaluronic Acid Nanoparticles Induces Epigenetic Changes with Altered Mitochondrial Bioenergetics and Apoptosis in Non-Small-Cell Lung Cancer Cells

Abstract: Therapies targeting epigenetic changes for cancer treatment are in Phase I/II trials; however, all of these target only nuclear DNA. Emerging evidence suggests presence of methylation marks on mitochondrial DNA (mtDNA); but their contribution in cancer is unidentified. Expression of genes encoded on mtDNA are altered in cancer cells, along with increased glycolytic flux. Such glycolytic flux and elevated reactive oxygen species is supported by increased antioxidant; glutathione. MicroRNA-34a can translocate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…In another study, it has been recently demonstrated that miRNA-34 encapsulated in hyaluronic acid nanoparticles is able to reduce intracellular GSH levels and Nrf2 expression, thus sensitizing Non-Small-Cell Lung Carcinoma (NSCLC) cells to the cytotoxic effects of cisplatin [ 150 ].…”
Section: Mirna Therapy: a Promising Strategy In Treatment Of Cancer Amentioning
confidence: 99%
“…In another study, it has been recently demonstrated that miRNA-34 encapsulated in hyaluronic acid nanoparticles is able to reduce intracellular GSH levels and Nrf2 expression, thus sensitizing Non-Small-Cell Lung Carcinoma (NSCLC) cells to the cytotoxic effects of cisplatin [ 150 ].…”
Section: Mirna Therapy: a Promising Strategy In Treatment Of Cancer Amentioning
confidence: 99%
“…The activities of NAG and acid phosphatase enzymes in hippocampal sections were measured using colorimetric analysis with commercial kits available from Abcam and Biovision, respectively. The LAMP1, LAMP2, NAG and acid phosphatase gene expression levels were measured using qPCR as described previously ( Trivedi et al, 2017 ). Protein expression was evaluated using western blot as previously described ( Talekar et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Solid lipid nanoparticles, neutral lipid nanoparticles, hyaluronic acid nanoparticles [30][31][32] miR-29b Cationic lipoplex nanoparticles [32] iNOP-7-PLK1 siRNA (polo-like kinase 1 siRNA) Nanoparticle-7 (iNOP-7, a highly branched generation four poly-L-lysine dendrimer [33] long-circulating siRNA Cationic lipid/solid polymer hybrid [34] TUSC2-expressing plasmid DNA Nanovesicles of N-[1-(2,3-dioleoyloxy)propyl]-N,N,N-trimethylammonium chloride (DOTAP):cholesterol (DOTAP:chol) [35] Plasmid DNA Liposomal nanoparticles containing cationic lipid, 6-lauroxyhexyl lysinate (LHLN) [36] p53-EGFP plasmid DNA Solid lipid NPs composed of 3β-[N-(Nʹ,Nʹ-dimethyla-minoethane)-carbamoyl]cholesterol hydrochloride (DC-Chol), 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) and Tween 80 [37] EGFP plasmid DNA Lecithin-based SNLs [37] 2ʹ-O-methyl-RNA (AON) Chitosan-modified PLGA nanoparticles [38] miR-497 Exosomal vehicles ii) Polymeric nanomaterials Polymeric nanomaterials can be synthesized using synthetic or natural polymers, showing diversity in their shape, size, and structure. They can be formed using one of the two methods, that is, precipitation or emulsion method through self-assembly of the co-polymers, which greatly affect their physiochemical properties.…”
Section: Mir-34amentioning
confidence: 99%